Stock Price Volatility Assesed From Aspects Devidend Yield and Earnings Volatility in Companies Listed in Indonesia Stock Exchange - Riri Mayliza; Nanda Suryadi; Arie Yusnelly (Asosiasi Dosen Akuntansi Indonesia, 2020)
Stock price volatility is the movement of rising or falling stock prices. This study aimed to obtain empirical evidence about the effect of dividend yield and earnings volatility on stock price volatility in companies listed on the Indonesia Stock Exchange (BEI) for the 2014-2018 periods. The sample in this study was 9 companies selected by purposive sampling method with 4 years of observation, namely 2014-2018. The analytical method used was the panel data regression method. Based on the hypotheses, the results of the study show that dividend yield does not significantly affect stock price volatility and earnings volatility has a significant effect on stock price volatility.